Charge‐coupled device based on optical tomography system for monitoring two‐phase flow - J. Jamaludin; R. Abdul Rahim; H. Abdul Rahim; M.H. Fazalul Rahiman; J. Mohd Rohani (Electronics Letters)
An application of charge‐coupled device (CCD) linear sensor and laser diode in an optical tomography (OPT) system is presented. The measurements are based on the final light intensity received by the sensor. The aim is to analyse and demonstrate the capability of laser with a CCD in an OPT system for detecting transparent objects in crystal clear water. The image reconstruction algorithms used were filtered images of linear back projection algorithms. These algorithms were programmed using LabVIEW programming software. Experiments in detecting transparent hollow straw were conducted. Based on the results, statistical analysis was performed to verify that the captured data were valid compared with the actual object data. The object's characteristics such as diameter also are observed. In conclusion, a non‐intrusive and non‐invasive OPT system that can detect transparent objects in crystal clear water is successfully developed.